Coffee and Its Flavor - Baiq Rien Handayani (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2016)
Coffee is one of the most widely served beverage. Flavor mainly the aroma is the most important attribute to specialty coffee. Coffee flavor consisted of volatile and non volatile compounds. The compounds were influenced by several factors i.e. growth environment, physiology, harvesting, post-harvest, roasting process and preparation.